Prolonged ER Stressed-Hepatocytes drives an Alternative Macrophage Polarization - Xiu, Fangming (Shock, 2015)
Relatively little is known about the effects of hepatocytes on hepatic macrophages, particularly under the situation of endoplasmic reticulum (ER) stress. We examined the effects of hepatocytes conditioned media (CM) from HepG2 treated with ER stress inducers, Tunicamycin (TM) or Thapsigargin (TG), on the secretion of cytokines, expression of ER stress markers and polarization of PMA activated THP-1 cells (pTHP-1). We found that CM decreased the production of the pro-inflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin (IL)-6 and interleukin (IL)-1β as well as other cytokines and chemokines from pTHP-1 cells. These effects are mediated by the inhibition of TLR4 expression and NF-κB signaling pathway. In addition, hepatocytes CM increased the expression of binding immunoglobulin protein (BiP) and the transcription factor C/EBP homologous protein (CHOP) in pTHP-1 cells. Preconditioning with ER stress inhibitor, small molecular chaperone 4-phenylbutyrate (PBA) before addition of ER stressors, attenuated the ER stress in macrophages, the property of hepatocytes CM to alter TNF-α production and NF-κB expression by macrophages. Remarkably, treatment of macrophage with these CM leads to an alternative activation of macrophages mediated by peroxisome proliferator-activated receptor-γ (PPAR-γ) signaling pathway, which might be resulted from the secretion of IL-10 and IL-4 as well as releasing apoptotic bodies from hepatocytes under ER stress. Our results highlight a mechanism of ER stress transmission from hepatocytes to macrophage that drives an alternative activation of macrophages, which depends on the exposure of hepatocytes to severe and prolonged ER stress.